Revolutions of All Colors : A Novel - Farria, Dewaine (Book collections on Project MUSE., 2020)
""Revolutions of All Colors" is a novel that follows the lives of three black Americans as they confront the uniquely American dilemma of cobbling together an identity in a country still struggling to define itself. Farria stitches together myriad points of view and overlapping time-frames to tell a story of evolving masculinity and friendship in the midst of racial and sexual politics, fatherhood, and war"--